Risk Mitigation Strategies in Information Systems Continuity Plans for Public Institutions: The case if Industrial Development Zones (IDZs) - Tom, Mbulelo (Department of Information Systems, 2019)
Information systems (IS) and new technologies have become an integral part of conducting business in today’s world. Almost all organisational sectors have adopted the use of IT systems and applications to conduct business and stay competitive in the industry within which they operate. However, if not well managed, Information Technology (IT) usage has the potential to expose organisations to various threats and vulnerabilities, which can have disastrous consequences. A risk mitigation plan is a strategy that helps an organisation to deal with a wide range of unexpected events. It covers a long-term plan and strategy that acts as a safety net to both avert a disaster and ensure long term survival. The purpose of this study is to examine risk factors and associated mitigation strategies in public organisation. The case study is the Industrial Development Zone (IDZ) of South Africa. The study had two objectives: (i) identify risks associated with IDZ; and (ii) examine how IDZ address risk mitigation strategies. A qualitative enquiry was used to carry out the study. Data was collected via interviews that were conducted with executive and other key managers from the IDZ. The study identified human, organisational and technological risk factors as those that impact mitigation strategies in public institutions of South Africa. Proposed contextual solutions for these challenges included: (i) the adoption of mobile solutions and on-going research of new mobility solutions so as to keep up to date with technological advancements; (ii) the regular update of security policies of the organisation so as to align with environmental challenges; and (iii) on-going continuous security checks to evaluate and test disaster preparedness. Awareness of tools and applications used to address mitigation was seen as a key technological factor. This study contributes to a better explanation of the challenges faced by IDZs in the developing country of South Africa, and puts forward recommendations for practice.